Application of intrinsically conducting polymers in flexible electronics. (18th August 2021) - Ouyang, Jianyong
Abstract: Intrinsically conducting polymers (ICPs), such as polyacetylene, polyaniline, polypyrrole, polythiophene, and poly(3, 4‐ethylenedioxythiophene) (PEDOT), can have important application in flexible electronics owing to their unique merits including high conductivity, high mechanical flexibility, low cost, and good biocompatibility. The requirements for their application in flexible electronics include high conductivity and appropriate mechanical properties. The conductivity of some ICPs can be enhanced through a postpolymerization treatment, the so‐called "secondary doping." A conducting polymer film with high conductivity can be used as flexible electrode and even as flexible transparent electrode of optoelectronic devices. The application of ICPs as stretchable electrode requires high mechanical stretchability. The mechanical stretchability of ICPs can be improved through blending with a soft polymer or plasticization. Because of their good biocompatibility, ICPs can be modified as dry electrode for biopotential monitoring and neural interface. In addition, ICPs can be used as the active material of strain sensors for healthcare monitoring, and they can be adopted to monitor food processing, such as the fermentation, steaming, storage, and refreshing of starch‐based food because of the resistance variation caused by the food volume change. All these applications of ICPs are covered in this review article. Abstract : Because they combine the merits of metals and plastics, intrinsically conducting polymers can have important application in flexible electronic devices and systems, such as flexible electrode particularly the transparent electrode of optoelectronic devices, stretchable electrode, dry biopotential electrode, neural interface, and strain sensors for healthcare monitoring and food processing monitoring.